[PP.18.04] CHRONIC URIC ACID ELEVATION IS ASSOCIATED TO BAROREFLEX IMPAIRMENT IN HYPERTENSIVE WOMEN. (September 2017) - Ramirez, A.; Christen, A.I.; Sanchez, R.A.
Abstract : Objective: Chronic plasma uric acid elevation is known to maintain hypertension and induces irreversible vascular damage and results in a form of salt sensitive hypertension. The mechanisms suggested are activation of the renin angiotensin system and inhibition of neuronal nitric oxide synthase, which is associated to incident hypertension particularly in younger individuals and women. Thus, the aim of this work was to evaluate the relationship of uric Acid and autonomic activity in hypertensive patients. Design and method: evaluated in 402 HT (242 Males, 55 ± 0.9y, BMI: 28.9 ± 0.3 Kg/m 2 ) and 160 Females (58 ± 1.0 y, BMI: 28.1 ± 0.4 Kg/m 2 ). with normal (<100 mg/dL) or higher (>100 mg/dL) glycemia, , the Autonomic Activity and the pulse wave velocity (PWV). In each patient blood samples were drawn for biochemical evaluations and 24 h blood pressure (BP) monitoring, PWV and BMI calculated. The vagal activation (Va) or inhibition (Vi), calculated as the slope (msec/mmHg) of the reflex response to spontaneous BP increase or decrease, represent the Autonomic Activity (1 h beat to beat BP signal recording). Results: In males mean BP was 131 ± 1.08 / 8308 / 83 ± 0.59 mmHg with a PWV equal to 9.16 ± 0.16 m/sec. In females, BP was 126 ± 0.88 / 77 ± 0.89 mmHg and PWV 9.01 ± 0.18 m/sec. The relationship between UA and metabolic parameters are shown in the following table: Figure. No caption available. BMI: Body Mass Index; Abd. Circ. Abdominal Circumpherence; HDLc: High Density Cholesterol; TG: Triglycerides; G120: Glycemia at 120 min after a Glucose Load (175 g); IB: Basal Insulin plasma Levels; Gly <100 mg/dL and Gly > 100 mg/dL means Glycemia Plasma Leves lower or higher than 100mg%, respectively. In women, UA was mainly related to Va (−0.371, p < 0.05) or Vi (0.271, p < 0.05). This correlation was stronger un subjects with glycemia >100 mg% (Va: 0.818, p < 0.001 or Vi: 0.56, p < 0.025) than for Normo glycemic subjects (r = 0.40/ r = −0.22). Conclusions: In hypertensive women uric acid is associated to decreased vagal activity which is know to be a predictor of cardiovascular mortality. These impairment which is higher in hyperglycemic hypertensives, supports previous information that women with hyper uricemia are at higher risk of coronary heart disease than men.